Parental Perspectives on Neonatologist Continuity of Care. (17th December 2021) - Machut, Kerri Z.; Gilbart, Christie; Murthy, Karna; Michelson, Kelly N.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Continuity of care (COC) is highly regarded; however, data about benefits are mixed. Little is known about components, parental views, or the value COC may provide to neonatal intensive care unit (NICU) infants and families. Purpose: To describe parents' perspectives on definitions, reasons they value, and suggested improvements regarding COC provided by neonatologists. Methods: We performed a qualitative study of in-person, semistructured interviews with parents of NICU infants hospitalized for 28 days or more. We analyzed interview transcripts using content analysis, identifying codes of parental experiences, expressed value, and improvement ideas related to neonatologist COC, and categorizing emerging themes. Results: Fifteen families (15 mothers and 2 fathers) described 4 themes about COC: (1) longitudinal neonatologists: gaining experience with infants and building relationships with parents over time; (2) background knowledge: knowing infants' clinical history and current condition; (3) care plans: establishing patient-centered goals and management plans; and (4) communication: demonstrating consistent communication and messaging. Parents described benefits of COC as decreasing knowledge gaps, advancing clinical progress, and decreasing parental stress. Suggested improvement strategies included optimizing staffing and sign-out/transition processes, utilizing clinical guidelines, and enhancing communication. Using parent input and existing literature, we developed a definition and conceptual framework of COC. Implications for Practice: NICUs should promote practices that enhance COC. Parental suggestions can help direct improvement efforts. Implications for Research: Our COC definition and conceptual framework can guide development of research and quality improvement projects. Future studies should investigate nursing perspectives on NICU COC and the impact of COC on infant and family outcomes.